Molecular phylogeny and a new Iranian species of Caudospora (Sydowiellaceae, Diaporthales) - Voglmayr, Hermann (Sydowia, 2018)
For the first time, molecular phylogenetic data on the peculiar diaporthalean genus Caudospora are available. Macro- and microscopic morphology and phylogenetic multilocus analyses of partial nuc SSU-ITS-LSU rDNA, cal, ms204, rpb1, rpb2, tef1 and tub2 sequences revealed two distinct species of Caudospora, which are described and illustrated by light and scanning electron microscopy. Caudospora iranica is described as a new species from corticated dead twigs of Quercus sp. collected in Iran. It differs from the generic type, C. taleola, mainly by coarsely verrucose ascospores. The asexual morph of C. taleola on natural substrate is described and illustrated. Caudospora taleola is neotypified, and it is recorded from Iran for the first time. Phylogenetic analyses of a multigene matrix containing a representative selection of Diaporthales from four loci (ITS, LSU rDNA, rpb2 and tef1) revealed a placement of Caudospora within Sydowiellaceae.